Estimation of dust related ice nucleating particles in the atmosphere: Comparison of profiling and in-situ measurements - Haarig, Moritz; Ansmann, Albert; Walser, Adrian; Baars, Holger; Urbanneck, Claudia; Weinzierl, B.; Schöberl, Manuel; Dollner, Maximilian; Mamouri, Rodanthi-Elisavet; Althausen, Dietrich (My University, 2019)
Vertical profiles of number concentrations of dust particles relevant for ice nucleation in clouds are derived from lidar measurements. The results are compared to coincidental airborne in-situ measurements of particle number and surface area concentrations in the dust layer. The observations were performed in long-range transported Saharan dust at Barbados and Asian dust at Cyprus. The Asian dust data analysis is ongoing. A comparison of Asian and Saharan dust will be given at the conference. Concentrations of ice nucleating particles in the order of 10 to 1000 per cm-3 in the dust layer are derived for a temperature of-25°C at Barbados. The method can be used to continuously monitor the concentration of ice nucleating dust particles vertically resolved from lidar measurements.
Keywords: Ice; Optical radar; Dust particle; Ice nucleation; In-situ measurement; Lidar measurements; Number concentration